Associations between the ALSFRS‐R score and urate levels during 12 months of edaravone treatment for amyotrophic lateral sclerosis: Post hoc analysis of ALSFRS‐R scores in clinical studies MCI186‐16, MCI186‐17, and MCI186‐19. Issue 5 (2nd September 2022) - Takahashi, Fumihiro; Kano, Osamu; Nagano, Yoshito; Yoneoka, Takatomo; Nelson, Sally; Ushirogawa, Yoshiteru
Abstract: Introduction/Aims: In this study we examined the relationship between urate levels at baseline and functional change measured by the Amyotrophic Lateral Sclerosis Functional Rating Scale—Revised (ALSFRS‐R) total score after edaravone treatment. Methods: Data from the edaravone trials MCI186‐16, MCI186‐17, and MCI186‐19 were analyzed, including the following treatment sequence groups: edaravone‐edaravone (EE, n = 113); edaravone‐placebo (EP, n = 45); and placebo‐edaravone (PE, n = 146). Subgroups were defined as low baseline urate (below the median value of 4.8 mg/dL) and high baseline urate (≥4.8 mg/dL). The differences in ALSFRS‐R total score change and urate change were evaluated using the mixed model for repeated measurement for overall population, by urate‐level subgroup, and by trial. Results: Compared with the PE group, the EE group showed a slower decline in ALSFRS‐R score, regardless of the urate baseline level, and a slower decline in urate level in the higher baseline urate subgroup. Smaller changes in ALSFRS‐R score and urate were observed in patients diagnosed with "probable, laboratory‐supported ALS." There was a positive correlation between changes from baseline to cycle 12 in urate levels and ALSFRS‐R score. Discussion: Edaravone treatment in ALS patients diagnosed with "definite ALS" or "probable ALS" showed slowing of disease progression, regardless of baseline urate level. In addition, because edaravone treatment was associated with a slower decline in urate level in the higher baseline urate subgroup and urate‐level changes were associated with changes in ALSFRS‐R score, urate level, and/or change may be one indicator in predicting disease progression after edaravone administration.